A 23-Year-Old Woman with Cerebellopontine Tumor Angle Sectio Caesaria Trans-peritoneal Profunda Surgery Over Oligohydramnios Indication - Paramita, Dina; Putera, Try Buana Tunggal (JAI (Jurnal Anestesiologi Indonesia), 2024)
Background: Primary tumor are rarely found in pregnancy. Treatment for intracranial tumors in pregnant woman is a challenge for anesthesiologists, obstetricians and neurosurgeons. A large size cerebellopontine angle (CPA) tumor can suppress the brain stem structure and cause death if not treated immediately. This makes the way we treat patients, when the delivery time and the surgical intervention we choose to be quite difficult.Case: A 23 years-old female patient using general anesthesia (GA) to accommodate profunda trans-peritoneal cesarean section (SCTP) in a 36 weeks pregnancy age, G1P0A0, ASA IIIE with CPA tumor and oligohydramnions.Disscussion: Brain tumor usually grow rapidly during pregnancy due to fluid retention, increased blood volume, and hormonal changes. There is no specific guidelines that explain the treatment of intracranial tumor in pregnancy. This patient suffers from CPA tumor and oligohydramnions so SCTP is required. We use GA for SCTP because it is safe for patients with intracranial tumor.Conclusion: Female G1P0A0, 23 years old, 36 weeks pregnancy age with CPA tumor was consulted by Obstetricians to Anesthesiologists to do SCTP with GA.